Juridical Review of the Strength of Electronic Evidence To Proof Online Lending Agreement - Meher, Montayana; Ginting, Lilawati (Faculty of Law, Universitas Pekalongan, 2024)
Online lending is a financial service provider for the community, with the granting of this online financial service license, it is hoped that the community, whose economy has been affected and has experienced setbacks during the Covid-19 pandemic, can be helped again to carry out their business activities. When viewed from the practical side, online loans are very helpful and make it easy for people to borrow money. Unlike banks or pawnshops that require a lot of administrative requirements and also collateral or collateral. The research in writing this scientific work is normative juridical research. Normative juridical research is research that examines the application of legal rules and norms related to the topic discussed. The nature of this research is descriptive, namely research that analyzes a legal regulation. All electronic documents in online lending and borrowing agreements that are affixed with valid electronic signatures and also carried out in accordance with the standard provisions stipulated in the Civil Code, ITE Law, and Financial Services Authority Regulations, are valid and strong as electronic evidence and have the same position as letter evidence. Therefore, every online lending and borrowing agreement in which the customer defaults, can file a lawsuit for default to the district court with initial evidence in the form of electronic documents.